PENGARUH USIA DAN PARITAS TERHADAP KEJADIAN PRE EKLAMPSIA DI RSUD SIDOARJO - Novianti, Hinda (Jurnal Ilmiah Kesehatan, 2016)
The Influence Of Age And Parity Of Events Pre Eklampsia In Sidoarjo General Hospital. One of the complications in pregnancy that could have an impact on maternal neonatal mortality is preeclampsia. Until now, the exact cause of preeclampsia is not known. The purpose of this study was to determine the effects of age and parity on the incidence of preeclampsia. The study design was cross-sectional analytic approach. Entire population Pregnant women and maternity hospitals in the delivery room of Sidoarjo by 450 people from January to March 2016, samples were taken using simple random sampling of 150 respondents. The independent variables were maternal age and parity, the dependent variable was the incidence of preeclampsia. The research instrument used secondary data from medical records. Then the data is processed with the process of editing, coding, processing and cleaning, were analyzed using univariate, bivariate and multivariate analysis with multiple logistic regression. Results of the research that has been conducted using the chi-square test for variables of age obtained Pearson chi-square value of 24.093 and p = 0.000> 0.05 of the proceeds Ho is rejected, and the variable parity performed using chi- square test of Pearson chi-square didapatkannilai 8.687 and p = 0.000> 0.05 from the results of Ho rejected. From the multiple logistic regression multivariate analysis showed calculation results Nagelkerke R 0234 square connotes age and parity variables simultaneously able to explain 23.4% of variations in the risk of preeclampsia. In conclusion there is the effect of age on preeclampsia, and there is also the effect of parity against preeclampsia.